2005
DOI: 10.1007/s00467-005-2040-4
|View full text |Cite
|
Sign up to set email alerts
|

C1Q nephropathy in children

Abstract: C1q nephropathy (C1qNP) is a peculiar form of glomerulonephritis characterized by mesangial immunoglobulin and complement deposits, predominantly C1q, with no evidence of systemic lupus erythematosus. We describe the incidence, manifestation, histopathologic findings, follow-up, treatment and outcome of C1qNP. Twelve C1qNP patients were identified among 131 children who had undergone renal biopsy, accounting for a 9.16% incidence of C1qNP. Light microscopy examination showed focal segmental glomerulosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We also found 3 more patients who could be diagnosed with IgMN according to IF criteria [ 16 ]. However, the inconsistency of diagnosis of IgMN and C1qN was not a problem in our study alone, since many other studies also used different criteria for the diagnosis of IgMN and C1qN [ 14 16 , 18 21 , 28 ]. We assume this reflects the uncertainty of IgMN and C1qN as distinct clinical disease entities [ 13 , 15 , 29 ].…”
Section: Discussionmentioning
confidence: 75%
“…We also found 3 more patients who could be diagnosed with IgMN according to IF criteria [ 16 ]. However, the inconsistency of diagnosis of IgMN and C1qN was not a problem in our study alone, since many other studies also used different criteria for the diagnosis of IgMN and C1qN [ 14 16 , 18 21 , 28 ]. We assume this reflects the uncertainty of IgMN and C1qN as distinct clinical disease entities [ 13 , 15 , 29 ].…”
Section: Discussionmentioning
confidence: 75%
“…Another possibility for why our eligible cases did not experience abnormal urinalysis is that immunosuppressive therapy against rejection might suppress the inflammation, although Kersnik Levart et al reported that cyclosporine A and/or mycophenorate mofetil were not effective for some cases of C1qN [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological findings described in patients with C1qN have usually varied with minimal change disease and FSGS being reported most commonly [ 2 , 4 , 6–8 , 10 ]. In a study by Markowitz et al , as many as 17 out of the 19 patients with C1qN had FSGS on renal histopathology.…”
Section: Discussionmentioning
confidence: 99%